Identification and Risk Management Strategy in MSMEs of Vegetable Traders: A Case Study of Pak Marbun at KM 55 Dayun Market - Jumiati Sasmita; Agnees Doriyanti; Tasya Erina; Rizky Pratama (JURNAL MANAJEMEN RISIKO, 2025)
This study aims to identify the various types of risks faced by MSMEs vegetable traders and analyze the risk management strategies applied, with a case study on Pak Marbun's business in the KM 55 Dayun Market. The research method used was qualitative descriptive through direct interviews and SWOT analysis. The results of the study show that MSMEs vegetable traders face market, financial, marketing, operational, human resources, and legal risks. The highest risk identified is the emergence of many new competitors. The main strength of the business is the completeness of the product and the strategic location, while the weaknesses include perishable goods and the absence of financial records. The risk management strategies implemented include focusing on basic necessities, providing alternative goods, and efforts to have supplier reserves. The conclusion of this study is that risk identification and the implementation of appropriate risk management strategies, such as product diversification and financial recording, are crucial for the sustainability of MSMEs and vegetable traders in the face of market dynamics